Using Real-Time Tracking of Materials and Labor for Kit-Based Logistics Management in Construction - Zhao, Jianyu; Zheng, Yuan; Seppänen, Olli; Tetik, Müge; Peltokorpi, Antti (Frontiers in Built Environment, 2021)
Improved productivity and the elimination of waste are key goals for lean methods in construction production control. One such lean method is a kit-based logistics management in which task-based materials are delivered just-in-time (JIT) and aligned with assembly operations on-site. Digital platforms could enable a situational awareness of work and material flows, potentially increasing the benefit and applicability of kitting. The aim of the current research is to utilize a real-time indoor tracking of material and labor flows to evaluate an assembly kit–based management of construction projects. We propose a linked data framework to connect labor, material, and scheduling information to integrate heterogenous data. The contribution of the study is threefold: first, a feasible method is developed to enable real-time detection of work and material flows inside the building for logistics management purposes. Second, several key performance indicators (KPIs) for effective evaluation of kit-based production flow in construction are provided, which allows management to tackle root causes of problems and to enhance timely and productive logistic solutions. Thirdly, by applying the linked data method, the study introduces a novel approach to integrate heterogenous data from both indoor tracking and schedules.